The Effectiveness of Project-Based Learning (PjBL) Assisted by Canva Digital Media in Enhancing the Ability to Create Advertisements, Slogans, and Posters among Eighth-Grade Students In V SMP Negeri 9 Kotamobagu, North Sulawesi - Endah As'ari Ramlie; Donal Ratu; Fince Sambeka (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the effectiveness of the Project-Based Learning (PjBL) model assisted by Canva digital media in improving the ability of eighth-grade students to create advertisements, slogans, and posters. This research employed a true experimental design with a pretest-posttest control group design. The study was conducted at SMP Negeri 9 Kotamobagu, Indonesia. The population consisted of all eighth-grade students, from which a sample of 49 students was randomly assigneHere is a summary of the thesis written in the format of a scientific article for an international journal. Keywords: Project-Based Learning, Canva, Advertisements, Slogans, Posters, Digital Media, Experimental Research